Diffusion and association processes in biological systems: theory, computation and experiment - Mereghetti, Paolo; Kokh, Daria; McCammon, J. Andrew; Wade, Rebecca C. (BMC Biophysics, 2011)
Macromolecular diffusion plays a fundamental role in biological processes. Here, we give an overview of recent methodological advances and some of the challenges for understanding how molecular diffusional properties influence biological function that were highlighted at a recent workshop, BDBDB2, the second Biological Diffusion and Brownian Dynamics Brainstorm.